CENDAWAN PENYEBAB ABORTUS DALAM ALAT REPRODUKSI SAPI BETINA - Djaenudin Gholib; Riza Zainuddin Ahmad (BERITA BIOLOGI, 2013)
The study on cases of abortion in cow caused by fungi have never been reported so far in Indonesia. The aim of this research is to get prevalence of cows have not and have aborted, both have reproductive disorder, and health cattles associated with percentage of fungi isolated.The study included both field survey and laboratory examination of samples. The samples of vaginal fluid were collected by using cotton swabs in cow which had suffered abortion or cow had repeated breeding, as well as freeze dried semen for artificial insemination (AI), and also examining the occurrence of abortion in cattle. The samples were collected in Sukabumi and Bandung, and then cultured in Sabouraud Dextrose Agar by stretch method, followed by incubation at 37oC. Number of samples collected consisted of 56 samples of cattle which had suffered from abortion and cow that had reproductive problems; 38 samples as control; five samples of freeze dried semen. There were no cases of abortion observed when field survey was conducted, therefore organ samples were not available for pathological and histophathological examination. Further examination on growth rate of yeast showed 20% of yeast presented in cows with abortion, 17% in cows with reproductive problem and 14% in normal cattle. On the other hand,there were samples that did not show any growth of yeast recorded f rom cows with abortion (15%)cattle with reproductive problem (7%) and normal cows (27%). Meanwhile, only twowith 2 yeast growth observed in semen samples. It was concluded that samples from cattles with reproductive problems (with and without aborted experiences) showed higher number of growth of yeasts compared with normal cow (P<0,05). Freeze dried semen were having risk of contamination by yeasts. There was no different on growth rate of fungi between reproductive problem and with abortion cow (P>0,05).